Filamentous Fungal Human Pathogens from Food Emphasising Aspergillus, Fusarium and Mucor - R. Russell M. Paterson; Nelson Lima (Microorganisms, 2017)
Disease caused by filamentous fungal human pathogens (FFHP) is increasing. These organisms cause severe mycoses in immunosuppressed individuals, such as those: (a) with AIDS; (b) having undergone transplantation; and/or (c) undergoing chemotherapy. Immunocompetent people can become infected. Some FFHP are isolated from foods which may be fomites. However, the information concerning particular species on specific food is large, dispersed and difficult to obtain. Reports of filamentous fungi from food/crops and causing human disease are frequently only available in the literature of food mycology/plant pathology and medical mycology, respectively: it is seldom cross-referenced. Aspergillus contains some species with strains that are the most dangerous FFHP, with Aspergillus fumigatus causing the most serious diseases. Fusarium and Mucor also contain species of high importance and approximately 15 other genera are involved. A checklist and database of FFHP species isolated from food is presented herein with emphasis on Aspergillus, Fusarium and Mucor in summary tables to increase awareness of the connection between food and FFHP. Metadata on all FFHP is provided in a large supplementary table for updating and revision when necessary. Previous names of fungi have been revised to reflect current valid usage whenever appropriate. The information will form a foundation for future research and taxonomic revisions in the field. The paper will be highly useful for medical practitioners, food mycologists, fungal taxonomists, patients, regulators and food producers interested in reducing infectious diseases and producing high quality food.